Biosafety Protocols in Dental Care: a Bibliographical Review - Gianela Lorleyn Sánchez Erazo; Karen Estefanía Chicaiza Bonilla; Gissele Alejandra Villarruel Andrade; Pedro Leonardo Padilla Proaño (Medisur)
The biosafety protocols in dental care in the face of the COVID-19 pandemic, in medical offices in Los Ceibos sector of Ibarra city during the period October 2021 to March 2022 had deficiencies, they do not have enough information about their application. The stated objective was the biosafety protocol’s evaluation for dental care in the Los Ceibos sector. In this research, methods of the theoretical level have been used; as well as the empirical level, which are applied with their respective instruments, such as the interview guide and the questionnaire. With this preliminary result, it is concluded that the knowledge of the inhabitants about these protocols is regular. At the doctor's office does not possess all of the level of requisite information to achieve the effectiveness of the protocols so that a revision of the existent bibliography prevails over the theme to complement its implementation. 23 documentary sources was consulted, 18 of them in Spanish and 5 in English among primary sources and secondaries as well as another one back up acceded by means of the principal managers of quest.